2010
DOI: 10.1007/s10803-010-0936-8
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Predicting Inner Speech Use Amongst Children with Autism Spectrum Disorder (ASD): The Roles of Verbal Ability and Cognitive Profile

Abstract: Studies of inner speech use in ASD have produced conflicting results. Lidstone et al., J Autism Dev Disord (2009) hypothesised that Cognitive Profile (i.e., discrepancy between non-verbal and verbal abilities) is a predictor of inner speech use amongst children with ASD. They suggested other, contradictory results might be explained in terms of the different composition of ASD samples (in terms of Cognitive Profile) in each study. To test this, we conducted a new analysis of Williams et al.'s, J Child Psychol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…Recent research has yielded a high level of agreement between clinical and research diagnoses (Mazefsky & Oswald, 2006). In line with other recently published studies (e.g., Franklin, Sowden, Burley, Notman, & Alder, 2008;Williams & Jarrold, 2010), therefore, the official diagnosis from an experienced, trained clinician and the nonverbal and face recognition data collected here were considered sufficient background information for the current report.…”
Section: Participantssupporting
confidence: 65%
“…Recent research has yielded a high level of agreement between clinical and research diagnoses (Mazefsky & Oswald, 2006). In line with other recently published studies (e.g., Franklin, Sowden, Burley, Notman, & Alder, 2008;Williams & Jarrold, 2010), therefore, the official diagnosis from an experienced, trained clinician and the nonverbal and face recognition data collected here were considered sufficient background information for the current report.…”
Section: Participantssupporting
confidence: 65%
“…They found no group differences in recall performance, but when subjects were divided by their verbal mental age (VMA), those with VMA over 7 years had better overall recall performance and a significant phonological similarity effect but no visual similarity effect, while subjects with VMA less than 7 years exhibited the opposite pattern. In other words, this study found VMA to better predict strategy use than did diagnostic group, and additional analyses found VMA to be a better predictor than cognitive profiles as well (Williams and Jarrold 2010). While the authors of this study did not discount the significance of cognitive profile in predicting strategy use, they cautioned against treating it as the only variable of relevance, and they also pointed out the importance of looking at variables like VMA and cognitive profile, in addition to diagnostic group, in assessing results in experimental studies of autism.…”
Section: Serial Recallmentioning
confidence: 51%
“…Indeed, the disruption of inner speech has been shown to affect performance on a cued attention task where the cue required a degree of decoding, such as in the present study (i.e. retrieving the association between a symbolic cue and the appropriate task) [Miyake et al., ], and inner speech has been hypothesized to be reduced in ASD participants [Lidstone et al., ; Wallace et al., ; Whitehouse et al., ; Williams & Jarrold, ]. Alternately, the nature of the observed correlation between VIQ and alpha modulations in ASD could be mediational in nature insofar as ASD individuals with high verbal ability could use inner speech to compensate for dysfunction elsewhere in the cortical networks of executive function and selective attention.…”
Section: Discussionmentioning
confidence: 90%